Pronunciation of English Fricatives by Indonesian EFL Learners: Patterns and Pedagogical Implications - Sabbu, Sukma Widya Sasmi; Rahman, Nadya Septiani; Mbau, Anitha Thalib; Nurlaela, Nurlaela (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Pronunciation plays a vital role in oral communication; yet, many Indonesian learners of English as a Foreign Language (EFL) continue to face difficulties, particularly in articulating fricative consonants that are absent from their native language. This study investigates the pronunciation problems experienced by second-semester students of the English Department at Makassar Muhammadiyah University, with a specific focus on English fricative consonants. Employing a mixed-method approach, data were gathered through a pronunciation test, interviews, and audio recordings. The findings indicate that dental fricatives /θ/ and /ð/ are the most problematic, often substituted with /t/ and /d/ due to first-language interference and limited exposure to pronunciation models. Additional contributing factors include a lack of articulatory awareness, insufficient phonetic training, and minimal practice. These results suggest the need for more explicit instruction and guided pronunciation practice to improve learners’ phonological competence. The study provides practical insights for English instructors to enhance pronunciation-focused pedagogy and curriculum development